Update on Enamel Bonding Strategies - Sato, Takaaki; Takagaki, Tomohiro; Hatayama, Takashi; Nikaido, Toru; Tagami, Junji (Frontiers in Dental Medicine, 2021)
Optimal strategies for the application of an adhesive differ between enamel and dentin because of the differences in composition. The development of adhesive systems has mainly focused on bonding of dentin, rather than enamel, by etching with phosphoric acid (PA). Dental adhesive technologies continue to rapidly advance, and various adhesive systems have been developed since the Buonocore’s study in 1955. He introduced the enamel acid etch technique. Then, the etch-and-rinse (ER) system was developed, and the subsequent self-etch (SE) system. Universal adhesives are a new generation of one-bottle SE adhesives that can be applied with either ER mode or SE mode, or a combined system involving selective enamel etching mode. Because the combination of PA etching and an SE system differs from conventional ER systems, the enamel bonding strategy should be carefully considered. This concise review of the literature on reliable enamel bonding strategies should prove helpful to clinicians to choose an appropriate adhesive system to achieve optimal clinical outcomes.